2012
DOI: 10.1111/j.1752-4571.2012.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

A new heterogeneous family of telomerically encoded Cryptosporidium proteins

Abstract: Cryptosporidiosis is predominantly caused by two closely related species of protozoan parasites the zoonotic Cryptosporidium parvum and anthroponotic Cryptosporidium hominis which diverge phenotypically in respect to host range and virulence. Using comparative genomics we identified two genes displaying overt heterogeneity between species. Although initial work suggested both were species specific, Cops-1 for C. parvum and Chos-1 for C. hominis, subsequent study identified an abridged ortholog of Cops-1 in C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…These characteristics suggested a possible role in host-parasite interactions, and we undertook a further characterization of the Cops-1 protein. Consistent with such a role, Cops-1 appears to be a secreted protein localized to the oocyst content and sporozoite surface of C. parvum but not C. hominis (165). Additionally, sera from C. parvum-infected patients recognized a 50-kDa protein in antigen preparations of C. parvum but not C. hominis, consistent with Cops-1 showing species-specific expression and being antigenic for patients (165).…”
Section: Contingency Genesmentioning
confidence: 49%
See 1 more Smart Citation
“…These characteristics suggested a possible role in host-parasite interactions, and we undertook a further characterization of the Cops-1 protein. Consistent with such a role, Cops-1 appears to be a secreted protein localized to the oocyst content and sporozoite surface of C. parvum but not C. hominis (165). Additionally, sera from C. parvum-infected patients recognized a 50-kDa protein in antigen preparations of C. parvum but not C. hominis, consistent with Cops-1 showing species-specific expression and being antigenic for patients (165).…”
Section: Contingency Genesmentioning
confidence: 49%
“…However, when tested experimentally, the majority of the genes were found to be present in both species albeit with slight interspecies and intersubtype sequence variability. Nevertheless, PCR results showed experimental evidence for one C. hominis-specific and C. parvum-specific genes (165). A subsequent study by Widmer and colleagues which also aimed to investigate the genetic basis of Cryptosporidium host specificity used genome-wide comparisons of C. parvum zoonotic, C. parvum anthroponotic (IIc subtype), and C. hominis isolates (166).…”
Section: Genomics Of Cryptosporidium Speciesmentioning
confidence: 99%
“…In C. hominis , Chro50011 is the last gene in chromosome 3 whereas Chro.50010 is the second-to-last gene in chromosome 5. The latter also has some sequence similarity to cgd2_4380, which is the last gene in chromosome 2 of C. parvum and was identified initially as a C. parvum -specific gene (Cops-1), but is known to have an orthologue in some C. hominis specimens (Bouzid et al, 2013). In C. parvum , an abridged, unannotated orthologue of Chro.50010 exists near the end of chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that telomeric/subtelomeric regions are highly polymorphic and might encode putative virulence factors ( 33 , 34 ). However, these studies did not compare phenotypic differences among isolates, and data for the present study do not relate directly to sequence variations at telomeres.…”
Section: Discussionmentioning
confidence: 99%